2004
DOI: 10.1016/j.ejcts.2004.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Repair of transposition of the great arteries, ventricular septal defect and left ventricular outflow tract obstruction

Abstract: The Lecompte procedure and Rastelli repair provide satisfactory early and late results. However, substantial late morbidity is more associated with conduit obstruction, and LVOTO in Rastelli repair rather than Lecompte procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 21 publications
2
44
0
Order By: Relevance
“…Hörer et al reported a 5-year freedom from RVOT re-operation of 49%; freedom from reoperation for LVOTO was 93% [2]. The overall freedom from re-operation (mainly for RVOTO) as reported by Lee et al was 40% at 5 years [12]. Although the results of the Rastelli procedure were slightly better in our own study, at 15 years, freedom from RVOT re-intervention was also no more than 21%.…”
Section: Discussionmentioning
confidence: 68%
“…Hörer et al reported a 5-year freedom from RVOT re-operation of 49%; freedom from reoperation for LVOTO was 93% [2]. The overall freedom from re-operation (mainly for RVOTO) as reported by Lee et al was 40% at 5 years [12]. Although the results of the Rastelli procedure were slightly better in our own study, at 15 years, freedom from RVOT re-intervention was also no more than 21%.…”
Section: Discussionmentioning
confidence: 68%
“…In fact, Rastelli operation was associated with a greater risk of reintervention due to left ventricular outflow tract obstruction, and extracardiac conduit problems such as obstruction, requiring eventual replacement. However, similar early and late mortalities were reported [43,44]. The Nikaidoh's procedure is also an option in the setting of discordant ventriculoarterial connections, ventricular septal defect and left outflow tract obstruction, especially if inadequate anatomy for a REV or Rastelli is present [45].…”
Section: Corrective Treatmentmentioning
confidence: 80%
“…2 We modified the Lecompte procedure without applying the Lecompte maneuver. We reported early and midterm results for the modified Lecompte procedure, [12][13][14] which was also compared with the Rastelli procedure, 14 but its long-term results have not been reported. 15 We started to apply the modified Lecompte procedure in 1988.…”
Section: Resultsmentioning
confidence: 99%